PENENTUAN STRATEGI DENGAN PENDEKATAN ANALISIS SWOT PADA HOTEL NONGSA POINT MARINA & RESORT DALAM MENGHADAPI PERSAINGAN BISNIS - Riszky Ramadhan Nourlette; Shinta Wahyu Hati (Politeknik Negeri Bengkalis, 2017)
Abstract :This study aimed to determine the external and internal condition of Nongsa Point Marina & Resort Hotel as the basis of defining a strategy to face the competition. The method used in this study is qualitative descriptive approach. Primary and secondary data is processed to gather information about the strengths and weaknesses and the opportunities and threats of Nongsa Point Marina & Resort Hotel. The result of this study is the competitive strategy which must be applied is market penetration. This result is obtained through a series of processes from SWOT Analysis which is started from analyzing the internal and external factors until defining a strategy with QSPM matrix. Keywords: Hotel, SWOT Analysis, QSPM Matrix